Dynamic behaviors of micro air bubbles in a stagnant vertical water reactor - Winarto, Felixtianus Eko Wismo (2012)
Milli and micro size bubbles show altogether different dynamic behavior in a vertical water column. Millimeter size air bubble adds turbulence and acts as water stirrer, due to high velocity components (horizontal and vertical) and frequent shape change. These parameters add an influence of high buoyancy force and low surface tension. A reduction in the bubble size (milli to micro) tends to change the upward velocity, buoyancy force, drag force and exhibit a little or no turbulence effect. An experimental setup was established to study the development of fine air bubbles in a stagnant vertical water column. Porous sintered glasses with porosities of I to 40 µm, were used as diffuser to produce micro bubbles. To close to the real wastewater physiochemical characteristics, the Glycerin in various volume fractions of 0.1 % to 0.5% in distilled water was used. The relationships between Froude number and bubble velocity as well as Reynolds number and bubble diameter, show that the higher pollutant concentration in the water solution would decrease the bubble diameter and reduce the vertical velocity. These parameters (bubble diameter and vertical velocity) lead to high effectiveness of suspended particle separation, and are validated by measuring the low concentration of pollutant (PPM). Keyword : milli and micro bubble, turbulence effect, porous sintered glass, submerged diffuser, polvdispcrscd. polluted willer, froude number, PPM decreasing.